The Place of The Constructed Devices Designed for the Development of the Student's Creative Activity in Experimental Problems (Journal of Pedagogical Inventions and Practices, 2022)
An important factor in ensuring high efficiency in teaching physics is the effective use of demonstrative experimental problems, educational films, ,. Every theory, law, physical phenomena and concepts that are explained theoretically during the training will reach a logical conclusion only after being proven by experimental problems, and will have a strong place in the student's mind